AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN SPEAKING ENGLISH ABOUT ASKING AND GIVINGINFORMATION OF SMAN 1 PULAU PUNJUNG - Cindy Aurellya; Feby Meuthia Yusuf; Sherly Franchisca; Lailatul Husna; Yessy Marzona (Ekasakti Educational Scientific Journal, 2024)
Based on experience of the observation during as junior teacher in SMA N 1 Pulau Punjung. The researcher found the students have difficulties in speaking. Based on that problem the researcher tried to analyze students' speaking skills by presenting and the conversation included asking the information in that conversation. There are 3 problems were mentioned such as: (1) the students had problem with their confidence to take a part in the conversation, (2) students were not familiar with what expressions should be said when asking information and (3). the teacher did not apply varied and effective techniques in teaching speaking. This research was conducted in SMAN 1 Pulau Punjung in academic year 2022/2023. The research method used is descriptive research method, where this Research involved 18 students took the test. The population in this research was 16 students first year of English department. In taking the sample, the researcher used random sampling. The research instrument used was a speaking test which involved several components in the speaking score rubric. This data collection, the researcher asked the students to perform the speaking performance by including the asking and giving information expressions. In evaluating the test, the researcher focused on the five criteria of speaking itself; pronunciation, fluency, grammar, vocabulary and comprehension. From the result of the research showed that students’ speaking skill was good the average score got by the English student in English speaking performance. The average score was 72.7. this score categorized as moderate. The most difficult component faced by the students was grammar component, where the students only got 14,1 in percentage. It menas that this component was the most difficult for the students. So, the students difficulties in speaking skill through task based learning is grammar.